High density of fox and cat faeces in kitchen gardens and resulting rodent exposure to Echinococcus multilocularis and Toxoplasma gondii - Bastien, Matthieu; Vaniscotte, Amelie; Combes, Benoit; Umhang, Gerald; Germain, Estelle; Gouley, Valentin; Pierlet, Alice; Quintaine, Thomas; Forin-Wiart, Marie-Amelie; Villena, Isabelle; Aubert, Dominique; Boue, Franck; et al. (Folia parasitologica, 2018)
The faeces of the red fox, Vulpes vulpes (Linnaeus), and the domestic cat, Felis catus (Linnaeus), can be responsible for spreading eggs of Echinococcus multilocularis Leuckart, 1863 and oocysts of Toxoplasma gondii (Nicolle et Manceaux, 1908) into the environment. The accidental ingestion of these eggs or oocysts, through consumption of raw fruits or vegetables grown in or in contact with contaminated soil, can lead to alveolar echinococcosis (AE) or toxoplasmosis in humans. The present study provides a quantitative assessment of the faecal deposition by foxes and cats in kitchen gardens where fruits and vegetables are grown and its consequences for zoonosis transmission. The density of definitive host faeces is considered as one of the main factors in infection risk for intermediate hosts. The density of fox and cat faeces, as well as the prevalence of both AE and toxoplasmosis in rodent populations (contaminated by ingestion of eggs or oocysts), were compared within and outside kitchen gardens. Our results showed that the mean density of fox faeces did not significantly differ between kitchen gardens and habitat edges (0.29 ± 0.04 faeces/m2 vs 0.22 ± 0.02 faeces/m2), the latter being known as an area of high fox faeceal densities. The density of cat faeces was significantly higher within the kitchen garden than outside (0.86 ± 0.22 faeces/m2 vs 0.04 ± 0.02 faeces/m2). The sampled kitchen gardens might therefore be considered as possible hotspots for both fox and cat defecation. Of the 130 rodents trapped, 14% were infected by at least one species of fox or cat intestinal parasite. These rodents were significantly more often infected when they were exposed to a kitchen garden. These results suggest that the deposit of fox and cat faeces in kitchen gardens would significantly impact the risk of human exposure to E. multilocularis and T. gondii. and should be prevented using effective means.
Keywords: Echinococcus multilocularis; Animals; rodent prevalence; Gardens; Female; nemoci hlodavců; feces; Feces; Prevalence; Rodent Diseases; ženské pohlaví; Murinae; lišky; Francie; Toxoplasma; food-borne agents; Arvicolinae; parasite transmission risk; toxoplazmóza zvířat; echinokokóza; Cats; Echinococcosis; prevalence; fox faeces density; Male; Foxes; France; Toxoplasmosis, Animal; zvířata; mužské pohlaví; cat faeces density; kočky; zahrady